Techno-economic analysis of cutting-edge PV systems deployment and reconfigurations on rooftop industrial building in Saudi Arabia’s eastern region - Abdulrhman Klifa Al-Hanoot; Hazlie Mokhlis; Saad Mekhilef; Mohammad Alghoul; Hussain Shareef; Zaid Alotaibi (Energy Conversion and Management: X)
This study conducts an in-depth analysis of the energy performance and economic feasibility of utilizing five cutting-edge PV systems on the rooftop of an industrial building spanning approximately 29,000 m2 in Abqaiq City, Saudi Arabia. The primary focus lies in evaluating the performance of these systems within the local grid’s conditions, with an average monthly electrical consumption of 534,000 kWh/month. Using PVsyst software, simulations are carried out for five configurations representing advanced PV technologies. The objective is to determine the most efficient technology and scenario under the project’s environmental conditions. Installation costs, maintenance expenses, revenue estimates, and potential revenue sources are also factored in, considering local regulations and policies. By meticulously simulating and comparing five advanced PV technologies across various configurations, the research identifies the N-type Mono BIFACIAL module in the third configuration scenario as the most effective. This configuration demonstrated an impressive annual energy yield of 5,568 MWh, a high-performance ratio of 94.2 %, and an economically favourable Levelized Cost of Energy (LCOE) of $0.014/kWh. Additionally, it achieved a significant Net Present Value (NPV) of $5,084,516, a robust Return on Investment (ROI) of 431.9 %, and a short payback period (PBP) of 4.7 years. The overarching goal of this study is to provide informed investment decisions aimed at selecting the most suitable PV technology and configuration for the harsh coastal climate conditions prevalent in the region. Special consideration is given to meeting daytime electrical consumption needs while taking into account subsidies on electrical tariffs for the industrial sector in Saudi Arabia.